Water, sanitation, and hygiene (WASH) factors associated with stunting among under-fives: A hospital-based cross-sectional study in Banda Aceh, Indonesia - Desi Purnama Sari; Sulaiman Yusuf; Rusdi Andid; Dora Darussalam; Herlina Dimiati; Eka Yunita Amna (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Stunting remains a major public health threat among children under five years of age in developing countries, including Indonesia. Studies have shown that water, sanitation, and hygiene (WASH) interventions are essential for reducing the prevalence of the disease. This study aimed to identify WASH-related risk factors associated with stunting among under-fives. This hospital-based cross-sectional study included 133 randomly sampled children who attended outpatient clinics or were admitted for treatment at Rumah Sakit Umum Daerah (Regional Public Hospital-RSUD) dr. Zainoel Abidin Banda Aceh between April and May 2024. Data were collected using structured questionnaires and anthropometric measurements. The bivariate chi-square test and multivariate logistic regression analysis were used to analyze the data. Statistical significance was set at P < 0.05, with a 95% confidence interval (CI). The results showed that the prevalence of stunting was 35.3% among children under fives attended RSUD dr. Zainoel Abidin Banda Aceh. Bivariate analysis showed that stunting was associated with the main source of drinking water p=0.04, OR 2.29 (95% CI = 1.07 – 4.89). Multivariate regression analyses revealed the WASH-related risk factor for stunting, which was the child’s fecal disposal p= 0.03, OR= 0.26 (95% CI 0.08 – 0.85). In conclusion, child’s fecal disposal is a WASH-related risk factor for stunting among children who attended RSUD dr. Zainoel Abidin Banda Aceh. This risk factor can be modified through health policies that consider WASH interventions to manage stunting prevalence.",